If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(x + -6) = 0.3 Reorder the terms: glo(-6 + x) = 0.3 (-6 * glo + x * glo) = 0.3 (-6glo + glox) = 0.3 Solving -6glo + glox = 0.3 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -0.3 + -6glo + glox = 0.3 + -0.3 Combine like terms: 0.3 + -0.3 = 0.0 -0.3 + -6glo + glox = 0.0 The solution to this equation could not be determined.
| 34=q-14 | | u+17=88 | | 3x-14=41 | | 5(2-2x)=-20 | | -7(2x-3)+3=10-7(-2x-1) | | d+72=46 | | f(1)=-x+10 | | 1/2z=3/4 | | 4=(2x)^2/3 | | -6(3x+8)=-210 | | s+40=-32 | | -3(2x-1)=-63 | | f-11=60 | | p+1.8=19.95 | | 2(2t-5)(t+2)=0 | | 4-3w=56 | | 6-3x=5x-10x-10 | | 2x+11=1x+26 | | f+-30=-67 | | ab+c=f | | G(x)=3f(x)+1 | | 1/3x^1/2=4 | | 1n+72=23 | | x-8=4x-2 | | f(-3)=-x+10 | | 15-43=3(x-1)-4 | | 121c^2-36w^2=0 | | W(6)=250*6 | | 19=p+1 | | -6+3x+8=-210 | | 8a-(-3a)= | | 2x^4+3x^3-2x^2+14x+15=0 |